PENGARUH BRAND DESTINATION DAN PRODUK WISATATERHADAP NIAT BERKUNJUNG KEMBALI MELALUI WORD OF MOUTH (STUDI PADA OBJEK WISATA PANTAI KARANGTAWULAN KABUPATEN TASIKMALAYA) - Yani Restiani Widjaja (Universitas Putera Batam, 2018)
The tourism industry has an important role in the development of a region. Even in some areas shows that the tourism industry is able to boost the region from backwardness become the main source of income. The purpose of this study is to determine the effect of brand destination and tourism products on the intention of visiting again through word of mouth (study on pantai karangtawulan) . Basically Tasikmalaya Regency has interesting tourism potential and can be developed. A concept of brand destination, based on passion and interesting identity that are interconnected with various things that will make it easier for people to have an association with the place. Brand destination is believed to have the power to change perceptions and change a person's perspective on a place or a destination including seeing the difference of a place with another place to choose as a destination. This type of research is eksplanatory research, where the data collection technique used is a questionnaire tool, Sample selected amounted to 100 people with accidental sampling and purposive sampling. The respondents are visitors of the beach resort of karangtawulan who have been to the beach. Based on this, the authors suggest that the management of beach attractions karangtawulan to further improve tourism products, which is to increase the direction of the road to the beach tawulan coral, adding public facilities for the end of the tourist attraction, improve tourist attractions, improve facilities and more active in offering a guide to visitors , so it can increase tourists visit karangtawulan beach.